Clinical outcome of patients with refractory Kawasaki disease based on treatment modalities - Hyun Jung Kim; Hyo Eun Lee; Jae Won Yu; Hong Ryang Kil (Korean Pediatric Society, 2016)
PurposeAlthough a significant number of reports on new therapeutic options for refractory Kawasaki disease (KD) such as steroid, infliximab, or repeated intravenous immunoglobulin (IVIG) are available, their effectiveness in reducing the prevalence of coronary artery lesions (CAL) remains controversial. This study aimed to define the clinical characteristics of patients with refractory KD and to assess the effects of adjuvant therapy on patient outcomes.MethodsWe performed a retrospective study of 38 refractory KD patients from January 2012 to March 2015. We divided these patients into 2 groups: group 1 received more than 3 IVIG administration+ steroid therapy, (n=7, 18.4%), and group 2 patients were unresponsive to initial IVIG and required steroid therapy or second IVIG (n=31, 81.6%). We compared the clinical manifestations, laboratory results, and echocardiographic findings between the groups and examined the clinical utility of additional therapies in both groups.ResultsA significant difference was found in the total duration of fever between the groups (13.0±4.04 days in group 1 vs. 8.87±2.30 days in group 2; P=0.035). At the end of the follow-up, all cases in group 1 showed suppressed CAL. In group 2, coronary artery aneurysm occurred in 2 patients (6.4 %). All the patients treated with intravenous corticosteroids without additional IVIG developed CALs including coronary artery aneurysms.ConclusionNo statistical difference was found in the development of CAL between the groups. Prospective, randomized, clinical studies are needed to elucidate the effects of adjunctive therapy in refractory KD patients.